Reid on olfaction and secondary qualities - Quilty-Dunn, Jake (Frontiers in Psychology, 2013)
Thomas Reid is one of the primary early expositors of the "dual-component" theory of perception, according to which conscious perception constitutively involves a non-intentional sensation accompanied by a noninferential perceptual belief. In this paper, I will explore Reid's account of olfactory perception, and of odor as a secondary quality. Reid is often taken to endorse a broadly Lockean picture of secondary qualities, according to which they are simply dispositions to cause sensations. This picture creates problems, however, for Reid's account of how we perceive secondary qualities, including odors. Given Reid's insistence that we come to be aware of odors only by inferring a causal relation to obtain between them and our olfactory sensations, it seems that he cannot allow for direct, noninferential perceptual awareness of odors. Since his general account of perception invokes noninferential perceptual beliefs to explain perceptual awareness, it seems that Reid must either reject this general account for the case of olfactory perception (and supplant it with something else), or else deny that we ever actually perceive odors. I will attempt to reconcile these ideas by appeal to Reid's doctrine of "acquired perception," which involves the incorporation of learned conceptual representations into perceptual states via perceptual learning. Reidian acquired perception enables genuine olfactory perceptual acquaintance with odors despite the dependence of the semantic properties of the relevant representations on causal relations to sensations. In exploring these issues, I hope to illuminate several features of Reid's account of perception and demonstrate its interest to contemporary theorizing about conscious perception--especially olfaction--in the process. Reid’s theory of olfaction remains a live, coherent option for present-day theorists.